2020
DOI: 10.1080/23322705.2020.1690097
|View full text |Cite
|
Sign up to set email alerts
|

Combatting Human Trafficking since Palermo: What Do We Know about What Works?

Abstract: In 2016, there were an estimated 40.3 million victims of modern slavery in the world, more than were enslaved during the Transatlantic Slave Trade. Since the adoption of the 2000 UN Trafficking Protocol, numerous efforts from inter-governmental agencies, governmental agencies, international non-governmental organizations (INGOs), and domestic non-governmental organizations (NGOs) have strived to combat the phenomena of human trafficking through legal-institutional means, direct interventions, and programs of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 19 publications
(27 reference statements)
0
23
0
1
Order By: Relevance
“…Yet, there is astonishingly limited evidence on "what works" to prevent these abuses or to address the consequences (4). In a recent systematic review including 90 reports on trafficking programs, the authors concluded that organizations are still "struggling to demonstrate impact and discern what works to combat human trafficking" (5). Similarly, a Rapid Evidence Review of interventions in South Asia noted that "...the outcomes from the reviewed studies alone cannot be used as recommendations for policy and practice on trafficking..." (6).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is astonishingly limited evidence on "what works" to prevent these abuses or to address the consequences (4). In a recent systematic review including 90 reports on trafficking programs, the authors concluded that organizations are still "struggling to demonstrate impact and discern what works to combat human trafficking" (5). Similarly, a Rapid Evidence Review of interventions in South Asia noted that "...the outcomes from the reviewed studies alone cannot be used as recommendations for policy and practice on trafficking..." (6).…”
Section: Introductionmentioning
confidence: 99%
“…Human trafficking is an international problem. In 2016, all over the world there were an estimated 40.3 million victims of modern slavery, which is more than were enslaved during the Transatlantic Slave Trade (Bryant, Landman, 2020). More victims of trafficking in human beings were reported to UNODC in 2016 than at any time over the past 13 years, which means that about 40% more victims were detected, as compared to 2011 (UNODC, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of trafficking in persons often occurs in vulnerable groups of society, especially women and children, because in Indonesian society, women in the family structure are often not the head of the household who have the power to make strategic decisions (Bryant & Landman, 2020)there were an estimated 40.3 million victims of modern slavery in the world, more than were enslaved during the Transatlantic Slave Trade. Since the adoption of the 2000 UN Trafficking Protocol, numerous efforts from inter-governmental agencies, governmental agencies, international nongovernmental organizations (INGOs.…”
Section: Introductionmentioning
confidence: 99%